2014
DOI: 10.5216/ree.v16i2.23300
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de vídeo educativo no comportamento de higiene bucal de pacientes hematológicos

Abstract: Efeito de vídeo educativo no comportamento de higiene bucal de pacientes hematológicos* Effects of an educational video on the oral hygiene of patients with hematologic disordersEfecto de video educativo en el comportamiento de higiene bucal de pacientes hematológicos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
3
0
9
Order By: Relevance
“…The strategy was well accepted. 7 Another study also used a video for guidance of patients undergoing cardiac catheterization diagnosis, whose results demonstrated the efficacy of this type of resource, similar to that observed in our study. 8 Corroborating these findings, a randomized clinical trial aimed at determining whether educational videos were superior to routine verbal discussion to inform emergency patients about the risks and benefits of using intravenous contrast in computed tomography (CT) scans showed that the percentage of correct answers given by the IG was greater than that of the CG (68.1 vs. 47.8%).…”
Section: Discussionsupporting
confidence: 76%
“…The strategy was well accepted. 7 Another study also used a video for guidance of patients undergoing cardiac catheterization diagnosis, whose results demonstrated the efficacy of this type of resource, similar to that observed in our study. 8 Corroborating these findings, a randomized clinical trial aimed at determining whether educational videos were superior to routine verbal discussion to inform emergency patients about the risks and benefits of using intravenous contrast in computed tomography (CT) scans showed that the percentage of correct answers given by the IG was greater than that of the CG (68.1 vs. 47.8%).…”
Section: Discussionsupporting
confidence: 76%
“…Estudos envolvendo a construção e a validação de vídeos educativos na área da saúde (13)(14)(15)(16)(17)(18)(19) , assim como neste estudo, baseou-se na metodologia proposta por Fleming, Reynolds e Wallace (7) , cujos passos contribuem para a construção de um material capaz de informar seu público alvo.…”
Section: Discussionunclassified
“…6 Among the various types of interventions, we highlight those that use audio and visual resources, such as educational videos, which are a possibility to direct educational activities with patients, families, students and professionals. [7][8][9][10][11][12] This modality of intervention is being widely developed, validated and used in nursing care actions, aiming to stimulate and strengthen the target audience, providing subsidies to develop coping, socializing and care strategies. 8,[12][13] Educational videos are intended not only to provide new knowledge, but also to strengthen existing ones, as well as to help patients and their families according to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] This modality of intervention is being widely developed, validated and used in nursing care actions, aiming to stimulate and strengthen the target audience, providing subsidies to develop coping, socializing and care strategies. 8,[12][13] Educational videos are intended not only to provide new knowledge, but also to strengthen existing ones, as well as to help patients and their families according to their needs. A study carried out with families who experience cancer illness and the use of colostomy reports that they suffer the initial impact when they are surprised by the diagnosis.…”
Section: Introductionmentioning
confidence: 99%